2023
DOI: 10.1021/acs.jafc.3c02275
|View full text |Cite
|
Sign up to set email alerts
|

Bruceine D Acts as a Potential Insecticide by Antagonizing 20E–EcR/USP Signal Transduction

Abstract: Bruceine D (BD) is an effective insecticidal compound found in the Chinese herb Brucea javanica (L.) Merr. BD inhibits the growth and metamorphosis of Plutella xylostella and Drosophila melanogaster; however, its target protein and the molecular mechanism of insecticidal activity remain unclear. In this study, proteins with high affinity for BD were screened using surface plasmon resonance and high-performance liquid chromatography coupled with matrix-assisted laser desorption/ionizationtime-of-flight mass spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
(81 reference statements)
1
3
0
Order By: Relevance
“…javanica (L.) Merr. have been reported to be due to the presence of Bruceine D and other substances effectively controlling agricultural pests such as the DBM. , According to our findings, incorporating BJO leads to a significant enhancement in the insecticidal effect of the β-CYP EC emulsion against DBM. The enhancement can be attributed to the presence of insecticidally active compounds, such as Bruceine D, in BJO, along with the superior leaf-wetting properties of β-CYP EC-2, enabling the leaves to accommodate a greater amount of β-CYP.…”
Section: Resultssupporting
confidence: 65%
“…javanica (L.) Merr. have been reported to be due to the presence of Bruceine D and other substances effectively controlling agricultural pests such as the DBM. , According to our findings, incorporating BJO leads to a significant enhancement in the insecticidal effect of the β-CYP EC emulsion against DBM. The enhancement can be attributed to the presence of insecticidally active compounds, such as Bruceine D, in BJO, along with the superior leaf-wetting properties of β-CYP EC-2, enabling the leaves to accommodate a greater amount of β-CYP.…”
Section: Resultssupporting
confidence: 65%
“…According to the electrophysiological experiments, Bruceine D demonstrated observable inhibition of the PxRDL1 receptor. Bruceine D demonstrated notable inhibitory effects on the PxRDL1 receptor 31 …”
Section: Discussionmentioning
confidence: 98%
“…In this study, we provide a perspective to explain the mechanism of growth inhibition activity focusing on the perspective of nutrient absorption and assimilation. Coincidentally, the latest reports revealed that bruceine D can inhibit insect growth and metamorphosis through inhibition of the expression of 20E response genes by antagonizing 20E−EcR/USP signal transduction 31 . This might explain the reason for disrupting the titer of ecdysone and juvenile hormone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…javanica Merr is a shrub and grows primarily in the wet tropical biome from tropical and subtropical Asia to North Australia. The typical active ingredients of the genus Brucea are quassinoids that exhibit various biological activities including antibacterial, antimalarial, antitubercular, anti-HIV, and anticancer activities . Currently, there are more than 10 quassinoids isolated, of which Bruceine A, C, D, and H, BR, and dehydrobrucatol have been found to display potent anticancer activities such as inhibiting cell proliferation, inducing apoptosis, inhibiting migration/invasion, inducing autophagy, and restraining angiogenesis .…”
Section: Discussionmentioning
confidence: 99%